2000
DOI: 10.1074/jbc.m004239200
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Lacking Superoxide Dismutase(s) Show Elevated Levels of “Free Iron” as Measured by Whole Cell Electron Paramagnetic Resonance

Abstract: A current hypothesis explaining the toxicity of superoxide anion in vivo is that it oxidizes exposed [4Fe-4S] clusters in certain vulnerable enzymes causing release of iron and enzyme inactivation. The resulting increased levels of "free iron" catalyze deleterious oxidative reactions in the cell. In this study, we used low temperature Fe(III) electron paramagnetic resonance (EPR) spectroscopy to monitor iron status in whole cells of the unicellular eukaryote, Saccharomyces cerevisiae. The experimental protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 50 publications
4
85
1
2
Order By: Relevance
“…cerevisiae and E. coli SOD mutants are more prone to mutations (Farr et al, 1986;Huang et al, 2003) and contain high levels of intracellular free iron, which is evidenced by their marked Fenton-dependent DNA damage (Srinivasan et al, 2000). Consistent with these observations, we showed that SOD mutants of C. glabrata exhibited not only high levels of O 2 $2 , but also sensitivity to DNA damage agents and a high mutation rate (Fig.…”
Section: Deletion Of Sods Causes Accumulation Of Osupporting
confidence: 76%
“…cerevisiae and E. coli SOD mutants are more prone to mutations (Farr et al, 1986;Huang et al, 2003) and contain high levels of intracellular free iron, which is evidenced by their marked Fenton-dependent DNA damage (Srinivasan et al, 2000). Consistent with these observations, we showed that SOD mutants of C. glabrata exhibited not only high levels of O 2 $2 , but also sensitivity to DNA damage agents and a high mutation rate (Fig.…”
Section: Deletion Of Sods Causes Accumulation Of Osupporting
confidence: 76%
“…For this reason, free iron is poised to participate in Fenton reactions and thereby contribute to mutation rates. Interestingly, this is not true of Saccharomyces cerevisiae, whose pools of free iron are predominantly oxidized (64). It is possible that in yeast this iron is localized in a compartment that lacks univalent reductants, thereby minimizing the impact of the iron upon oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 98%
“…There are previous reports that deletion of CuZn and/or manganese SOD genes leads to accumulation of free iron in S. cerevisiae cells (70,71). Thus it appears that Cap2-mediated repression of SOD gene expression could additionally mobilize iron in vivo.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%